Methods in chemical process safety. Volume 3, - Amyotte, Paul; Khan, Faisal I. (Elsevier Ltd. : Academic Press, 2019)
Methods in Chemical Process Safety, Volume Three, addresses the most important challenges, recent advancements and contributions in chemical process safety. The work helps researchers and professionals obtain guidance on the selection and practice of chemical process safety methods. Chapters in the book cover Experimental Methods, Hazard Identification, Risk Assessment, Safety Measures, Regulations, Guidelines and Standards, Emerging/Unique Scenarios, and more. Users will find a complete guide that presents tactics in process safety management that are now globally recognized as the primary approach for establishing a high level of safety in operations. As process safety is now a disciplined framework for managing the integrity of operating systems and processes handling hazardous substances, and because continued occurrence of major losses have had a significant impact on the industry's approaches to modern process safety, this book is a must have for those in the industry. --